Education and the Hong Kong umbrella movement. Issue 2 (28th January 2019) - Jackson, Liz; O'Leary, Timothy
Abstract: This special issue of Educational Philosophy and Theory considers the Hong Kong Umbrella Movement as an educational event, which has impacted attitudes and outlooks and conceptions of young people's role, of education, and of society. This essay serves as an introduction to the more substantive pieces that follow. It describes two alternative perspectives on youth civic engagement in Hong Kong historically; and in so doing, it addresses some of the challenges related to free academic expression that hinder scholarly research and publishing on the area of Hong Kong-China relations looking into the future. It concludes with a brief glimpse of the contributions that follow.